Change in ALT levels after administration of HMG‐CoA reductase inhibitors to subjects with pretreatment levels three times the upper normal limit in clinical practice. Issue 3 (6th March 2018) - Kim, Hyunah; Lee, Hyeseon; Kim, Tong Min; Yang, So Jung; Baik, Seo Yeon; Lee, Seung‐Hwan; Cho, Jae‐Hyoung; Lee, Hyunyong; Yim, Hyeon Woo; Choi, In Young; Yoon, Kun‐Ho; Kim, Hun‐Sung
Summary: Aim: Prescription of statins to patients with chronic liver disease whose alanine transaminase (ALT) is over three times the upper normal limit (UNL) is not recommended. In this study, we attempted to evaluate patients with baseline ALT levels > 3 × UNL who were prescribed statins without ethical problems, using electronic medical records. Methods: We enrolled subjects with ALT levels > 3 × UNL. The patients were divided into three groups consisting of those who had been taking agents affecting liver function (HEPA) and continued to do so after the statin prescription (HepCon), those who had not previously taken HEPA and began doing so after statin prescription (HepNew), and those who had never taken HEPA (HepNo). All ALT levels were determined within 3 months of statins administration, and changes were monitored. Results: From January 2009 to December 2012, 61 patients with baseline ALT levels > 3 × UNL were prescribed statins for the first time. During the 3‐month ALT monitoring, levels of the HepCon, HepNew, and HepNo groups decreased by 45 ± 8%, 64 ± 10%, and 42 ± 8%, respectively; however, intergroup differences were not significant ( P = .386). All the subjects who were administered statins showed improvement or maintained their ALT levels, except for two subjects, which showed deterioration. However, the ALT levels of the two subjects subsequently remained stable. Conclusion: It is not clear whether it is safe to prescribe statins to patients with ALT > 3 times the UNL. Our study showed that prescription of statins in combination with HEPA did not cause deleterious effects, suggesting that ALT levels > 3 times the UNL do not have harmful effects.